Mobile and wireless communications key technologies and future applications - Smyth, Peter (Institution of Engineering and Technology, 2004)
The following topics are dealt with: Future of mobile and wireless communications; optical radio-a review of a radical new technology for wireless access infrastructure; wireless LANs-present and future; future applications of bluetooth; ultrawideband and its capabilities; ad hoc wireless networks; scalability, capacity and local connectivity in ad hoc networks; the role of ad hoc networks in mobility; securing mobile ad hoc networks - a motivational approach; the use of satellite for multimedia communications; evolving systems beyond 3G-the 1st brain and mind projects; economic tussles in the public mobile access market; enabling applications deployment on mobile networks; the parlay API-allowing third party application providers safe and secure access to network capabilities; radio spectrum management for tetherless communications; mobile multimedia services; multimodality-the future of the wireless user interface; mobile video-streaming; a social history of the mobile telephone with a view of its future.